GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 93038 species occurrences available in GBIF matching the query: TaxonKey: Balaenoptera physalus (Linnaeus, 1758). The dataset includes 93038 records from 94 constituent datasets: 2 records from UAM Mammal Collection (Arctos). 4383 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 3 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 13 records from iNaturalist research-grade observations. 3 records from Geographically tagged INSDC sequences. 1 records from SBMNH Vertebrate Zoology. 26 records from Mammal collection, Natural History Museum, University of Oslo. 1 records from SOMBASE. 1 records from Western Australian Museum provider for OZCAM. 1 records from Zoology (Museum of Evolution - Uppsala). 1 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 78396 records from HMAP-History pf Marine Animal Populations (CoML). 12 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 1 records from NYSM Mammals. 1 records from IndOBIS, Indian Ocean Node of OBIS. 86 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 2 records from IWDG Ferry Survey sightings Data 2001 to 2013. 453 records from IWDG Casual Cetacean Sightings. 10 records from AMNH Mammal Collections. 29 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 7 records from CAS Mammalogy (MAM). 28 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from observe_tuna_bycatch_ecoscope. 1 records from Colección osteológica de mastozoología marina. 1 records from NatureServe Network Species Occurrence Data. 20 records from Seabirds of the Southern and South Indian Ocean. 23 records from Occurrences des observations de la campagne Suivi Aérien de la Mégafaune Marine en France métropolitaine (SAMM1 - Hiver 2011/2012). 4 records from Paleobiology Database. 5022 records from SEAMAP - marine mammals, birds and turtles. 4 records from IWDG Cetacean Strandings Database 2010-2014. 27 records from Macaulay Library Audio and Video Collection. 1 records from Vertebrate Paleontology Division, Yale Peabody Museum. 40 records from Norwegian Species Observation Service. 1 records from Merseyside BioBank - North Merseyside Mammals (verified). 1 records from Israel Nature and Parks Authority. 26 records from National Whale and Dolphin Sightings and Strandings Database. 27 records from ESAS cetacean sightings from 1980 to 2003.. 1 records from Mammifères sauf Chiroptères du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 167 records from PIROP (Shipboard Surveys). 1 records from Atlas of Mammals in Ireland 2010-2015. 7 records from MVZ Mammal Collection (Arctos). 2 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 4 records from LSUMZ Mammals Collection. 5 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 10 records from LACM Vertebrate Collection. 10 records from Whale log - observations from ANARE voyages. 68 records from Collection Anatomie Histologie - SMF. 2 records from MfN - Fossil vertebrates IV. 1 records from Colección de Mastozoología. 17 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 9 records from Lund Museum of Zoology (MZLU). 14 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 9 records from RBINS collections. 48 records from Museum of Comparative Zoology, Harvard University. 1 records from OEH Atlas of NSW Wildlife. 7 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 64 records from Naturalis Biodiversity Center (NL) - Mammalia. 2453 records from Whale catches in the Southern Ocean. 8 records from UWBM Mammalogy Collection. 5 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 4 records from University of California Museum of Paleontology. 1 records from DMNS Mammal Collection (Arctos). 1 records from Tasmanian Museum and Art Gallery provider for OZCAM. 8 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 5 records from UMMZ Mammal Collection. 4 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 6 records from Mammalogy Collection - Royal Ontario Museum. 3 records from CUMV Mammal Collection (Arctos). 42 records from Cetacean Sightings Survey and Southern Ocean Cetacean Program - BROKE-West. 4 records from NCSM Mammals Collection. 1 records from Cowan Tetrapod Collection - Mammals. 7 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 70 records from Cetacean Sightings Survey and Southern Ocean cetacean program. 182 records from Natural History Museum (London) Collection Specimens. 3 records from ANTXXIII-8 Birds and Mammals (SCAR-MarBIN: Antarctic OBIS). 12 records from South Australian Museum Australia provider for OZCAM. 79 records from IWDG Constant Effort Cetacean Sighting Scheme. 2 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 1 records from Bay of Fundy Species List (OBIS Canada). 6 records from CNMA/Colección Nacional de mamíferos. 5 records from naturgucker. 2 records from Australian Museum provider for OZCAM. 1 records from Fieldjournal.org observation database. 41 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 3 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 12 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 3 records from ANTXXIII-8 Birds and Mammals. 646 records from NMNH occurrence DwC-A. 71 records from PReCAST Marine Mammal Sightings. 23 records from Natural History Museum Rotterdam (NL) - Chordata collection. 2 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 157 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 56 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia.
Keywords: GBIF; biodiversity; species occurrences